2021
DOI: 10.1159/000518679
|View full text |Cite
|
Sign up to set email alerts
|

Innate Host Defense against <b><i>Klebsiella pneumoniae</i></b> and the Outlook for Development of Immunotherapies

Abstract: <i>Klebsiella pneumoniae</i> (<i>K. pneumoniae</i>) is a Gram-negative commensal bacterium and opportunistic pathogen. In healthy individuals, the innate immune system is adept at protecting against <i>K. pneumoniae</i> infection. Notably, the serum complement system and phagocytic leukocytes (e.g., neutrophils) are highly effective at eliminating <i>K. pneumoniae</i> and thereby preventing severe disease. On the other hand, the microbe is a major cause of health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 193 publications
(246 reference statements)
0
10
0
Order By: Relevance
“…Capsule Polysaccharide (CPS) production is one of the most important virulence factors of bacteria, which is involved in resistance to complement-mediated killing and neutrophil-mediated phagocytosis [ 17 ]. Several studies indicated that change in CPS production also affects the susceptibilities of some antibiotics, such as polymyxin, carbapenem, and tigecycline [ 18–20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Capsule Polysaccharide (CPS) production is one of the most important virulence factors of bacteria, which is involved in resistance to complement-mediated killing and neutrophil-mediated phagocytosis [ 17 ]. Several studies indicated that change in CPS production also affects the susceptibilities of some antibiotics, such as polymyxin, carbapenem, and tigecycline [ 18–20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As K. pneumoniae is a typical extracellular bacterium, the effect of cellular immunity on K. pneumoniae is relatively limited (Opoku-Temeng et al, 2022). Lee et al found that T-helper (T H ) lymphocytes played a prominent role in the defense of K. pneumoniae through secreting cytokines such as IL-17 and IFN-g (Lee et al, 2015).…”
Section: T Cell-mediated Immune Responsementioning
confidence: 99%
“…It is known that innate immunity and adaptive immunity are equally crucial in resisting pathogen invasion, the adaptive immune response is slower and more specific. Another prominent feature for adaptive immunity is the production of immunologic memory which is activated rapidly during reinfection, resulting in protective response ( Bonilla and Oettgen, 2010 ; Opoku-Temeng et al., 2022 ). Adaptive immunity includes T cell-mediated cellular response and B cell-mediated humoral response ( Bonilla and Oettgen, 2010 ).…”
Section: Adaptive Immune Response To K Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae has evolved into two pathotypes: classical and hypervirulent (hvKp) [4]. The classical K. pneumoniae is the leading cause of opportunistic healthcare-associated infections, such as urinary tract infections, pneumonia, wound and surgical site infections, and bacteraemia [5].…”
Section: Introductionmentioning
confidence: 99%